The Influence of Financial Indicators and Underwriter Reputation on Depreciated Stock Prices - Adi Gunanto (JAF (Journal of Accounting and Finance), 2023)
This research aims to analyze the influence of financial indicators and underwriter reputation on the level of stock underpricing during Initial Public Offerings (IPOs) on the Indonesia Stock Exchange (IDX). The phenomenon of underpricing has gained attention in securities market research in various countries. This study adopts a conceptual analysis approach based on a review of existing literature. The theory of asymmetric information also serves as the foundation for explaining the underpricing phenomenon in IPOs. Factors include Return on Equity (RoE), Financial Leverage, Current Ratio, Earnings per Share (EPS), Size, Proceeds, Company Age, Auditor Reputation, Underwriter, and Industry Type. Therefore, this research aims to test the influence of financial indicators and underwriter reputation on the level of stock underpricing in IPOs on the IDX. Consequently, the findings from this research can be used as a basis for comparison with similar studies in other countries. This can help in understanding the differences and similarities in the phenomenon of stock valuation in various global capital markets. Keywords: IPO Underpricing, Financial indicators and Underwriter reputation